2012
DOI: 10.1051/0004-6361/201220120
|View full text |Cite
|
Sign up to set email alerts
|

Observational constraints for the circumstellar disk of the B[e] star CPD−52 9243

Abstract: Context. The formation and evolution of gas and dust environments around B [e] supergiants are still open issues. Aims. We intend to study the geometry, kinematics and physical structure of the circumstellar environment (CE) of the B[e] supergiant CPD−52 9243 to provide further insights into the underlying mechanism causing the B[e] phenomenon. Methods. The influence of the different physical mechanisms acting on the CE (radiation pressure, rotation, bi-stability or tidal forces) is somehow reflected in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 29 publications
6
46
1
Order By: Relevance
“…As CO band emission typically arises from the inner rim/edge of the molecular disk region, the fact that our CO model temperatures are all much cooler than the dissociation temperature of 5000 K indicates that the material may be located in a detached disk structure, as opposed to a disk that reaches the stellar surface as suggested by the model of Zickgraf et al (1986). Such behavior has recently been reported in other studies Liermann et al 2010;Wheelwright et al 2012;Cidale et al 2012).…”
Section: Model Resultssupporting
confidence: 85%
“…As CO band emission typically arises from the inner rim/edge of the molecular disk region, the fact that our CO model temperatures are all much cooler than the dissociation temperature of 5000 K indicates that the material may be located in a detached disk structure, as opposed to a disk that reaches the stellar surface as suggested by the model of Zickgraf et al (1986). Such behavior has recently been reported in other studies Liermann et al 2010;Wheelwright et al 2012;Cidale et al 2012).…”
Section: Model Resultssupporting
confidence: 85%
“…The derived CO parameters (i.e., temperature and column density) are similar to those found for other B[e]SGs such as LHA 120-S 12 and LHA 120-S 73 in the Large Magellanic Cloud , LHA 115-S 65 in the Small Magellanic Cloud (Oksala et al 2012), and CPD-52 9243 (Cidale et al 2012) and MWC 349A (Kraus et al 2000) in the Galaxy. Only one Galactic object, HD 327083, seems to be extreme in the sense that its disk, studied by Wheelwright et al (2012), has the coolest (T CO = 1721 ± 540 K) and densest (N CO = (0.4 ± 1.8) × 10 24 cm −2 ) CO gas.…”
Section: Resultssupporting
confidence: 80%
“…Former calculations of CO emission from a disk revealed that it is sufficient to consider the innermost ring of gas with a constant temperature, column density, and rotation velocity (e.g., Kraus 2009;Liermann et al 2010;Cidale et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…We note that our derived IR luminosity is a lower limit of the total luminosity of the heating source, since we are only sensitive to warm (∼600 K) dust at 3.6 and 4.5 μm. Remarkably, the equilibrium temperature radius of surrounding dust (~-R 10 20 au eq ) matches the inner edge radii of spatially resolved galactic sgB[e] disks: 30 au for CPD-52 9243 (Cidale et al 2012) and~-20 30 au for MWC 300 (Wang et al 2012). X-1 is therefore a member of an emerging class of luminous X-ray sources with donor stars that resemble sgB[e] stars such as IGR J16318-4848 (Filliatre & Chaty 2004), GX 301-2 (Servillat et al 2014), and SN2010 da (Binder et al 2016;Lau et al 2016;Villar et al 2016).…”
Section: X-1 Donor: a Supergiant B[e] Star?mentioning
confidence: 67%